Moulting Greylag Geese Anser anser on Saltholm, Denmark do not cease feeding midday in response to diurnal oscillation in food quality - Fox, Anthony D.; Kahlert, Johnny (Wildfowl, 2015)
To seek support for the hypothesis that diurnal rhythms in protein and sugar levelsÂ in food plants were responsible for the largely nocturnal foraging of moultingÂ flightless Greylag Geese Anser anser (which ceased feeding to rest during the middleÂ part of the day), we sampled the laminae of Common Saltmarsh Grass PuccinelliaÂ maritima at two hour intervals over 24 h on 14 June 1998. There was no diurnalÂ pattern in the proportion of selected amino acids (including sulphur-containingÂ amino acids) in the laminae of this, the most important dietary item. Despite a cycleÂ in lamina sugar content that peaked at c. 18:00 h and was lowest at c. 06:00 h, thisÂ failed to explain why moulting geese ceased foraging in the middle of the day, whenÂ sugar levels were highest. Rather we contend that geese trade-off diurnal variation inÂ food energy content against the probability of lost time feeding to disturbance fromÂ predator-like stimuli, which were more common during the midday period. ElevatedÂ disturbance levels were the likely cause of geese roosting on offshore islands duringÂ daylight hours, despite increasing sugar levels in their food plants at this time. AÂ simple model demonstrated that geese potentially derived the same energy intakeÂ from soluble carbohydrates by feeding during the undisturbed period fromÂ 01:00â€“08:00 h (when food quality was lowest) as by foraging in the eveningÂ (18:00â€“01:00 h) when soluble carbohydrate content was highest and frequent daytimeÂ disturbance from helicopters had begun to decline.